Theoretical-conceptual approach to inclusive marketing: a perspective from sensory disabilities - Hincapié-Naranjo, Laura; Torres-Sarria, Sara; Castro-Peña, Mónica Yuleni; Vásquez-Hernández, John Eider (Clío América, 2024)
Individuals with sensory disabilities encounter barriers to communication and accessibility within the market due to the lack of inclusive marketing strategies. This oversight infringes on this demographic’s rights by failing to provide the necessary means to satisfy their needs, partly due to the limited access to information and knowledge about more inclusive marketing. Researchers chose a theoretical-conceptual approach to understand inclusive marketing, discussing the role that people with sensory disabilities have had within. This study employs statistical techniques and qualitative judgments based on bibliographic findings from a systematic search in the Scopus and Web of Science databases, utilizing the Core of Science tool. The study successfully identified a very narrow line of understanding between social marketing and inclusive marketing, establishing discussions and conclusions about the perception of inclusion in marketing and the vulnerable segments towards which the strategies and concepts developed so far have been directed.